On the Submission of Legal Terms in the Dictionary of International Words - Gedzevičienė, Dalia (Respectus Philologicus, 2023)
In order to determine whether the Dictionary of International Words (hereinafter TŽŽ2013) can be used as one of the sources of legal terminology in scientific and practical work, the terms denoting the concepts of law and their potential adjectival components were selected from the TŽŽ2013, the information provided with them was analysed, and the main features of the morphemic structure and semantics of the terms and their components were identified. Of the 676 legal terms found in the dictionary, 65% originate from Latin, 17% from French, 6.5% from Greek and 11% from other languages. The majority of legal noun terms are made up of all compounds with foreign roots, while all of the verb legal terms are to be regarded as hybrids since they are made up of a base with foreign roots and Lithuanian suffixes. 26% of the adjectival compounds are made of a foreign base and international suffixes, and around 70% are considered hybrids. The article also explores the discrepancies between the semantic fields of Lithuanian terms and their English equivalents. The TŽŽ2013, with certain reservations, can be used as one of the sources of legal terminology in law and language sciences as well as in practice.
Keywords: legal term; a dictionary of international words; word origin; morphemic structure; semantics